Analisis perbandingan alternatif investasi pada portofolio saham, mata uang dan komoditas emas dalam masa krisis keuangan global - ADRIANI, Dhanny ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The subprime mortgage crisis is an ongoing real estate crisis and financial crisis triggered by a dramatic rise in mortgage delinquencies and foreclosures in the United States, with major adverse consequences for banks and financial markets around the globe. The crisis, which has its roots in the closing years of the 20th century, became apparent in 2007 and has exposed pervasive weaknesses in financial industry regulation and the global financial system. Seeing from the current situation, analysis of several instrument investations are made in order to obtain result in what kind of instrument investation that has best performance in this global financial crisis. There also will be a hypotetical analysis to explain availability of impact and interaction between each instrument and its weekly return. Historical source of data are used in this research. Portofolio construction and calculation followed by statistical test are provided in this thesis. The analysis of variance (Anova) is used for statistical test.